Analisis Kritis Terhadap Pemikiran Utilitarianisme Jeremy Bentham dalam Perspektif Etika dan Filsafat Manusia - Rahman, Ayi; Maulana, Muhammad Falikh Rifqi (Journal of Society and Development, 2023)
Utilitarianism, introduced by Jeremy Bentham in the 18th century, proposes that the moral correctness of actions is judged on the basis of consequences that result in maximum happiness or well-being for the individuals involved, known as "the greatest happiness principle". However, the main criticism of this approach highlights the disregard for individual rights and the potential to justify unethical actions on the grounds of producing greater happiness overall. Criticism of Bentham's utilitarianism suggests that a focus on external consequences often overrides the internal moral values of an action, such as justice or moral obligation. The implication of this critique on modern understandings of justice, human rights, and moral values is the importance of considering deeper and broader moral aspects in ethical decision-making. In the face of the complexities of human life, not only the expected end result must be considered, but also fundamental moral principles such as individual human rights and just justice. A holistic ethical approach that integrates a variety of theories, including utilitarianism, deontology, and values approaches, is needed to provide a comprehensive understanding of the moral challenges faced by modern society. Thus, Bentham's critique of utilitarianism provides the basis for deeper reflection on the application of ethical principles in a broader and inclusive context..